Analysis of Administrative Processes in Goods Loading and Unloading Activities for Service Time Efficiency at the Warehouse of PT BGR Logistik Indonesia, DKI Jakarta Regional Division - Azra Karima Fasya (Asian Journal of Logistics Management, 2025)
Warehouse operations are a crucial part of the service process, not only in terms of administrative process of loading-unloading activities, but also in ensuring accuracy and efficient service time. This study aims to examine in greater depth the analysis of administrative and loading-unloading processes in relation to time efficiency in service delivery, so that warehouse operations can provide benefits through improved time efficiency. This research uses a qualitative method with a descriptive-analytical approach. The data sources include primary data collected through interviews and observations, as well as secondary data obtained from company documents and relevant literature concerning administrative process of loading-unloading. Data collection techniques involved field observations, interviews, and documentation. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The results of the research show that the administrative process mechanism in loading-unloading regarding time efficiency has not fully complied with the established standard operating procedures. However, there are obstacles within these processes that affect time efficiency, particularly due to delays in the issuance of delivery orders or work orders. Optimization efforts have been carried out to improve warehouse service time efficiency by identifying types and sources of waste and minimizing them through lean management methods. These efforts successfully reduced the number of process stages from 19 to 14 by eliminating wasteful activities.